Improving quality of life in female cancer survivors: current status and future questions. (June 2014) - Duska, Linda R; Dizon, Don S
ABSTRACT: : Almost 14 million people in the USA alone have been diagnosed with cancer. Given the improvements in diagnosis and treatment, over 60% of patients are expected to survive 5 years or more from the point of diagnosis. Treatments for cancer may result in long-term issues including those that impact the physical, emotional, spiritual or social domains. However, how best to care for issues in survivors remains unclear. Although much attention has been focused on survivorship care plans and survivorship clinics, there are limited data to show they improve outcomes. This article reviews the issues in female cancer survivors that can occur following diagnosis and treatment and suggest strategies that may assist in management. Finally, we review the current views regarding the care of cancer survivors and suggest important issues that must be addressed so that we can reach our goal of improvement in the quality of life of this emerging population.